Character building in the digital era: Strategies of aqidah akhlak teachers in an Indonesian islamic junior high school - Dila Novi Fitria; Gani Gani; Dewi Sela Eka Selvia; Abrar Hammadi Huwaimid Al-Harbi (CV. SPDFHarmony, 2026)
Background: The rapid expansion of digital technology has reshaped students’ learning environments and created new challenges for character education in Islamic schools. Social media, internet platforms, and digital communication increasingly influence students’ moral behaviour, requiring Aqidah Akhlak teachers to adopt strategies that keep Islamic values relevant in contemporary digital contexts.Aims: This study examines the pedagogical strategies used by Aqidah Akhlak teachers to foster students’ character, identifies the challenges encountered, and explores adaptive responses implemented in an Indonesian Islamic junior high school.Methods: A qualitative case study was conducted at MTs Darul Huda Sukabumi, Bandar Lampung. Participants were selected purposively and included an Aqidah Akhlak teacher, the headmaster, and seventh-grade students. Data were collected through semi-structured interviews, classroom observations, and document analysis, then analyzed using Miles, Huberman, and Saldaña’s interactive model.Results: Three themes emerged. First, character development was implemented through exemplary practice, habituation, contextualized moral instruction, and school–family partnerships. Second, implementation was challenged by digital influences, limited supervision outside school, and differing levels of family support. Third, teachers responded through persuasive moral guidance, continuous reinforcement, and collaborative monitoring involving parents and the madrasah. These findings show that character education becomes more effective when Islamic values are connected to students’ everyday digital experiences.Conclusion: Character education in Islamic junior high schools should extend beyond conventional religious instruction by integrating exemplary practice, contextual learning, sustained moral reinforcement, and collaboration among teachers, families, and schools.